Fatigue Assessment and Deterioration Effects on Masonry Elements: A Review of Numerical Models and Their Application to a Case Study - Casamassima, Vito Michele; D'Amato, Michele (Frontiers in Built Environment, 2019)
Safety assessment with respect to seismic and vertical loads of existing and very old masonry structures is currently a central topic of engineering scientific community. In particular, there are many ancient bridges still in service subjected, respect to the past, to higher and more frequent cyclic loads. For these structures it is really important to determine, rather than the ultimate carrying capacity, the actual fatigue strength. In this way the remaining service life, with also possible traffic load limitations, may be estimated. This paper reports an updated review of state of the art about the recent fatigue models published in the literature, taking also into account deterioration effects under cyclic loads. In addition, some results related to the fatigue performance of a case study are shown and commented. The numerical comparisons reveal that the application of the available fatigue model is particular problematic in the case of ancient masonry elements, where appropriate stress-life curves are required.